Tradução do prefácio de Bérénice, de Jean Baptiste Racine: Translation of the preface of Jean Baptiste Racine’s Bérénice - Amaral Tavares, Daniella (Rónai – Revista de Estudos Clássicos e Tradutórios, 2015)
Tradução do prefácio de Bérénice, de Jean Baptiste Racine.